Identifying the Key Concerns of Irish Persons with Intellectual Disability. - O'DOHERTY, SIOBHAN; GARCIA IRIARTE, EDURNE (My University, 2014)
BACKGROUND: Internationally, people with intellectual disability are socially marginalized, and their rights under the United Nations Convention for the Rights of Persons with Disabilities (CRPD) are often ignored. AIMS: This paper aims to define the key concerns of adults with an intellectual disability in relation to their participation in society using an inclusive research strategy for both data gathering and data analysis. METHODS: A national study involving 23 focus groups and 168 persons was conducted on the island of Ireland with people with intellectual disability as co-facilitators. FINDINGS: A thematic content analysis was undertaken of the verbatim transcripts initially by university co-researchers, and 19 themes were identified. Co-researchers with intellectual disability joined in identifying the eight core themes. These were as follows: living options, employment, relationships, citizenship, leisure time, money management, self-advocacy, and communication. DISCUSSION: The concerns are discussed within the framework of the CRPD, and implications for transforming service policy are drawn. ACCESSIBLE ABSTRACT: Why we did the research: In many countries, people with intellectual disability have difficulties doing things other people without disabilities do, for example to study, to get a job or to live independently. They also find that their rights are not respected under the Convention on the Rights of Persons with Disabilities (the Convention). We did this study to: Learn what are the main issues for adults with intellectual disability in Ireland. Do research with people with intellectual disability. How we did the research: People with intellectual disability and their supporters worked with university researchers to plan and do the research. We met with people in groups and 168 people told us about things important to them. What we found out: We found that there were very important things that people talked about in the groups. We chose the most important: living options, employment, relationships, rights, leisure, money, self-advocacy, and communication. We talk about the Convention and why things people told us are important for services.
PUBLISHED
Keywords: Ireland; Inclusive research; Intellectual disability; National survey